2011
DOI: 10.1364/ol.36.000852
|View full text |Cite
|
Sign up to set email alerts
|

Optical refractometer based on large-core air-clad photonic crystal fibers

Abstract: A large-core air-clad photonic crystal fiber-based sensing structure is described, which is sensitive to refractive index. The sensing head is based on multimodal interference, and relies on a single-mode/large-core air-clad photonic crystal fiber (PCF)/single-mode fiber configuration. Using two distinct large-core air-clad PCF geometries-one for refractive index measurement and the other for temperature compensation, it was possible to implement a sensing head sensitive to refractive index changes in water as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…In this line of research, at INESC Porto, in 2011 Silva et al reported the first MMI fiber-based refractometer which consisted in a SMS fiber structure relying on a large-core, air-clad photonic crystal fiber (PCF) [34]. This configuration is shown in Figure 5.…”
Section: Multimodal Interferencementioning
confidence: 99%
“…In this line of research, at INESC Porto, in 2011 Silva et al reported the first MMI fiber-based refractometer which consisted in a SMS fiber structure relying on a large-core, air-clad photonic crystal fiber (PCF) [34]. This configuration is shown in Figure 5.…”
Section: Multimodal Interferencementioning
confidence: 99%
“…However, the addition of the reference arm increased the complexity and unstability of sensing system. Silva et al demonstrated a sensor based on in series SMF-PCF(photonic crystal fiber)-SMF structure for the refractive index sensing with the ability of temperature compensation [22]. In their work, two pieces of large-core air-clad PCF with a larger diameter than SMF were employed, which would complicate the fabrication and increase the cost of the sensor.…”
Section: Introductionmentioning
confidence: 99%
“…In other work, a solid core PCF coated by SiNx nano film in same configuration of SMF-PCF-SMF that gave a maximum sensitivity 874 nm/RIU [10]. Also, a RI based sensor contains two large core and air clad of PCF is demonstrated that gave maximum sensitivity is 800 nm/RIU at resolution of about 3.4×10 -3 [11]. While, a hollow core based PCF was butt-coupled to SMF to achieve high sensitivity of about 5000 nm/RIU that showed interaction of measure with light [12].…”
Section: Related Workmentioning
confidence: 87%